Metabolismo da glicose cerebral no trauma crânio-encefálico: uma avaliação Cerebral glucose metabolism and head injury: an overview - AO. Schelp; R.C. Burini (Arquivos de Neuro-Psiquiatria)
Os autores apresentam revisão geral da distribuição e metabolização da glicose, com ênfase para os distúrbios que ocorrem no trauma crânio-encefálico, como a hiperglicemia que ocorre na fase aguda. Finalizando, são feitos comentários sobre as possíveis conseqüências desses conhecimentos sobre os procedimentos atuais, que aconselham a restrição na oferta de glicose a pacientes com catabolismo acentuado e que necessitam poupar o contingente de proteína corporal. The authors give a general overview on the cerebral glucose metabolism, with special reference to brain injury, including intake, blood-brain barrier properties for glucose transport, oxidative metabolism and energetic needs during the head trauma. The evidences of the presence of ischemia and hypoxia in those situations and the relationships with the cerebral glucose metabolism are discussed. They point to the several explanations for hyperglicemia present up to 10 days after admission in brain injury, relating to the energetic needs at different phases of head trauma recovery. Some considerations are made about the lack of evidences on increase in glucose consumption or lactate production when hyperglycemia occurs in association with brain damage and ischemia caused by head trauma. The brain capacity to compensate metabolic disturbances is discussed. Some questions are made about current indications for restriction of glucose infusion in pacients who are in catabolic phase and need to spare their body protein pool. At the same way, the polemic about previous hyperglycemia and cerebral injury is revised. Some considerations are made about the moment to introduct increases in glucose administration.